2021
DOI: 10.3390/ijms22116020
|View full text |Cite
|
Sign up to set email alerts
|

Role of Long Noncoding RNAs ZlMSTRG.11348 and UeMSTRG.02678 in Temperature-Dependent Culm Swelling in Zizania latifolia

Abstract: Temperature influences the physiological processes and ecology of both hosts and endophytes; however, it remains unclear how long noncoding RNAs (lncRNAs) modulate the consequences of temperature-dependent changes in host–pathogen interactions. To explore the role of lncRNAs in culm gall formation induced by the smut fungus Ustilago esculenta in Zizania latifolia, we employed RNA sequencing to identify lncRNAs and their potential cis-targets in Z. latifolia and U. esculenta under different temperatures. In Z. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Furthermore, it was shown that the bark storage protein is targeted in cis by one lncRNA. It was shown that the plant defense response is suppressed in Z. latifolia by lncRNA, which allows the symbiotic formation of the culm galls (Wang et al, 2021).…”
Section: Biotic Stressmentioning
confidence: 99%
“…Furthermore, it was shown that the bark storage protein is targeted in cis by one lncRNA. It was shown that the plant defense response is suppressed in Z. latifolia by lncRNA, which allows the symbiotic formation of the culm galls (Wang et al, 2021).…”
Section: Biotic Stressmentioning
confidence: 99%